Cervical cancer screening in Latin American countries from the perspective of health professionals - Laberiano Fernández, Caddie Dy (2020)
Objectives: To determine the status of cervical cancer screening in Latin American countries from the perspective of health personnel. Method: Online survey study of closed groups of pathologists and cytotechnologists. Results: 155 completed questionnaires were obtained. Most professionals surveyed considered that there are deficiencies in the screening of cervical cancer, such as poor approach and lack of staff training. Conclusion: It is necessary to invest financially in the policies created against cervical cancer.